Ruang Produksi dan Ruang Leisure: Praktik Konsumsi Pasar Senthir Beringharjo - Nadhilah Kusnad, Hajidah Kusnadi; Ayuningrum, Nara Garini (School of Communication Science and Media Business, 2025)
Pasar Senthir Yogyakarta, precisely located in the south parking lot of Pasar Beringharjo, is the object of research to be analyzed by researchers. Its uniqueness is the main attraction for researchers to discuss the form of consumption of space and pleasure in Beringharjo Senthir Market. Amid massive changes in technology and modernity, traditional markets, especially those selling second-hand goods, still exist and remain in demand among the public. By using the ethnography and production space theory of Henri Lefebvre, a Concept Triad of Production of Social Space, the discussion found that it was not only buying and selling activities that were carried out by the sellers and visitors to Senthir Market, but that they spent their free time reminiscing about ancient life. For older people, it is as if they are returning to memories, while for young people, they feel an atmosphere of the past that they could not have known and visited before. When buy an item, it is no longer only thinking about the function of the item, but also considering the sign value that is owned by the item purchased. A person's social status is judged by the goods he has.